2017
DOI: 10.4103/aer.aer_107_17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexmedetomidine on intraoperative hemodynamics and propofol requirement in patients undergoing laparoscopic cholecystectomy

Abstract: Background:Despite multiple benefits, laparoscopic surgery always poses anesthetic challenge due to significant alteration of hemodynamics. Various pharmacological agents have been used for the same with variable response. Dexmedetomidine, in addition to sympatholytic effect, diminishes intraoperative requirement of anesthetics including propofol. The present study was conducted to evaluate the effects of intravenous dexmedetomidine on intraoperative hemodynamics and propofol requirement using bispectral index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 36 publications
2
27
1
Order By: Relevance
“…Therefore, delirium, nausea, vomiting, and headache are all adverse reactions produced by traditional narcotics. 19 Herein, there were fewer adverse reactions after surgery in the study group, mainly because flurbiprofen axetil had no central effect and a strong sedative effect, which could significantly reduce the adverse reactions caused by propofol and after anesthesia.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, delirium, nausea, vomiting, and headache are all adverse reactions produced by traditional narcotics. 19 Herein, there were fewer adverse reactions after surgery in the study group, mainly because flurbiprofen axetil had no central effect and a strong sedative effect, which could significantly reduce the adverse reactions caused by propofol and after anesthesia.…”
Section: Discussionmentioning
confidence: 80%
“…However, in a research done by Khare and his colleagues [32] on non-MO patients, a significant less recovery time besides extubation time were found in dexmedetomidine group. This could be related to some degree by the lesser propofol requirement with the use dexmedetomidine as an adjunct medication.…”
Section: Tablementioning
confidence: 84%
“…P < 0.05 is significant. et al [23] found that recovery time was significantly less when dexmedetomidine was added to propofol infusion during laparoscopic cholecystectomy. Another study showed that recovery from anesthesia was faster when dexmedetomidine was used as adjunct during general anesthesia [24].…”
Section: Tablementioning
confidence: 99%